Recent trends in the international wine market and arising research questions - Eugenio Pomarici (Wine Economics and Policy, 2016)
Looking at the evolution of international wine trade over the last five years, the reduced growth rate and the varied performance of suppliers raise many research questions, at the micro- and macro-level. At the micro-level, research needs emerge regarding understanding consumer preferences, using innovative integrated approaches, and the exploitation of new paradigms concerning marketing strategies. At the macro-level, the key question concerns the possible evolution of international wine trade over the next 5-6 years, and the related consequences on the industry structure. Forecast of the future evolution of wine market is challenging and risky in a context dominated by discontinuities and there is not much research on how markets evolve. Nevertheless, wine economists should attend to this task with a wide multidisciplinary set of tools, also if imply an effort which is demanding and with uncertain results.
Keywords: 330; Experimental economics; International wine trade; Marketing strategy; Prospect theory